COMPARATIVE ANALYSIS OF METHODS OF SURGICAL TREATMENT OF VARICOCELE - Oleg I. Apolokhin; Evgeniy A. Efremov; Sergey Yu. Shekhovtsov; Yuriy V. Kastrikin (Креативная хирургия и онкология)
Introduction. Despite the fact that the existence of varicocele in puberty men, may be one of the risk factors of male infertility the mechanism of spermatogenesis breach remains unclear and should be proved further. Materials and methods. This study conducted a systematic review of randomized researches that are available on PubMed, with the purpose to analyze the optimum choice of surgical techniques to perform varicocelectomy on the basis of the presented results in men suffering from infertility.Results and discussion. According to the literature data the surgical treatment of varicocele in the presence of clinically significant forms leads to a significant improvement of spermatogenesis after 3-6 months surgical treatment. It is worth noting that the effectiveness of varicocelectomy significantly surpasses the results of drug stimulation of spermatogenesis and dynamic monitoring. At present, therefore it is significant to evaluate efficiency and the choice of the optimal method to surgically treat varicocele. According to the results of meta-analysis, it was concluded that the implementation of microsurgical subinguinal varicocelectomy has a number of advantages compared with such methods as Palomo surgery, laparoscopic varicocelectomy, Ivanissevich surgery and selective embolization of sperm veins.Conclusion. Application of microsurgical subinguinal varicocelectomy significantly improves quality and quantity parameters of sperm analysis and, consequently, increases probability of spontaneous pregnancy in partners with minimum percentage of complications, as well as of occurrence of relapse in postoperative period.